United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper on the United Kingdom finds that the main factors behind the slowdown include weak productivity growth, labor market slack, and low inflation. Recent labor market developments in the United Kingdom appear to point to disconnect between unemployment and wages. Although the unemployment rate has fallen to a 40-year low, wage growth continues to growth at a subdued pace. The analysis in this paper suggests that this puzzle is explained by persistent weak productivity growth and well-anchored inflation expectations, as well as by greater effective labor market slack than suggested by the headline unemployment rate. Broader measures of underemployment-accounting for involuntary part-time unemployment, inactive and self-employed people seeking regular jobs-suggest that slack in the labor market was higher than implied by the unemployment rate in recent years. Persistent tightness of the labor market should prompt some firming of wage growth in the coming year, everything else equal. A mild increase in unit labor costs would help bring domestically generated inflation in line with the inflation target.